2016
DOI: 10.17957/ijab/15.0210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Compost on Mung Bean Growth and Soil Properties in a Semi-arid Area of Northeast China

Abstract: Five treatments were performed to examine the effects of biochar and compost, applied separately or in combination, on plant growth of mung bean (Vigna radiata) and soil properties in a semi-arid area of northeast China. The results showed that biochar and compost produced positive impacts on both the plants and the soil, with these effects dependent upon the biochar to compost ratios. In addition, the changes in biomass and growth indices vary according to the growing phases: with the medium to late growing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Although biochar acts as the sink and the source of most available nutrients for the plant growth and yield, there was no significant difference in growth parameters and yield of lettuce. Our findings are consistent with the results of Awad et al (2017) and Wang et al (2016). From Table 3 and 4, this study observed that the application of biochar to the soil slightly increased growth and yield parameters but the effect was not significant (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Although biochar acts as the sink and the source of most available nutrients for the plant growth and yield, there was no significant difference in growth parameters and yield of lettuce. Our findings are consistent with the results of Awad et al (2017) and Wang et al (2016). From Table 3 and 4, this study observed that the application of biochar to the soil slightly increased growth and yield parameters but the effect was not significant (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Biochar was used to improve and improve the growth characteristics and quality of legumes. The addition of biochar to sandy soil boosted mung bean plant growth, biomass and yield 9,10 . Furthermore, biochar is very inert, with the majority of it staying in the soil for orders of magnitudes longer than any other organic amendment and biochar application to soils is usually associated with improved crop production 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of biochar led to improve and increased of growth parameters and quality of legumes Guerena et al, 2015). Application of biochar to sandy soil was increased plant growth, biomass and yield of mung bean (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%